التدفق النفسي وعلاقته بأداء مهارتي الاعداد واستقبال الارسال بالكرة الطائرة (Journal of the College of Basic Education, 2022)
Psychological flow and its relationship to the performance of the skills of preparing and receiving volleyball. Where the concept of psychological flow is one of the positive concepts, and in the sports side it has important dimensions, as it activates scientific interest in psychology and makes the behavioral construction of the sports personality so that it enables the player to face the difficulties in learning and since the volleyball game is one of the games that are characterized by difficult and changing situations, both during the learning process. Or play and these situations have a great impact on the behavior of the individual and therefore sportsconfidence is also one of the most important psychological phenomena, which is considered one of the main psychological features of the learnerFactors, the most prominent of which is the state of psychological flow, the researcher shed light on psychological flow by trying to find out the relationship between psychological flow and the performance of the skills of preparation and reception of the volleyball dispatch, as the psychological flow needs a person to exploit all his positive energies and that the effectiveness of the individual remains coexistent in the experience of psychological flow Until it reaches the status of completion, no matter how long the period of time Research objectives: The research aims to:Identify the correlational relationship between psychological flow and the performance of volleyball preparation skill in the research sample.Identify the correlation between psychological flow and performance of the volleyball dispatch reception skill for the research sample.The two research hypotheses:Identifying a statistically significant correlation between psychological flow and the performance of volleyball numbers for the research sample.Identifying a statistically significant correlation between psychological flow and the performance of the volleyball dispatch reception skill in the research sample.